Behaviour of normal reinforced concrete columns exposed to different soils - Rasheed Laith; Salih Shakir; Hanash Zahraa (MATEC Web of Conferences, 2018)
Concrete resistance to sulfate attack is one of the most important characteristics for maintaining the durability of concrete. In this study, the effect of the attack of sulfate salts on normal reinforced concrete column was investigated by burying these columns in two types of soils (sandy and clayey) in two pits at a depth of 3 m in one of the agricultural areas in the holy city of Karbala, one containing sandy soil (SO3 = 10.609%) and the other containing clayey soil with (SO3 = 2.61%). The tests were used (pure axial compression test of reinforced concrete columns, compressive strength test, and splitting tensile strength test, absorption, voids ratio and finally density). It`s found that the strength of RC columns decreasing by (12.51%) for age (240 days), for columns buried in clayey soil, where the strength increased by (11.71%) for the same period, for columns buried in sandy soils, with respect to the reference column.